Soil organic carbon drivers in a high-stock forested region - Toro Manríquez, Mónica del Rosario (2025)
Forests are pivotal in stocking Soil Organic Carbon (SOC). This study investigated the drivers influencing SOC stock in Chilean Patagonia, a region known for its extensive carbon reserves. We analysed the SOC stock (tons ha−1 at 30 cm depth) as the target variable, considering factors such as forest types (Nothofagus pumilio = NP, N. antarctica = NA, N. dombeyi-N. betuloides = ND-NB, evergreen = EV, and mixed broadleaved forests = MI), soil types (Andosols, Entisols, Inceptisols, and Spodosols), and human impacts (unmanaged = U, burned = B, harvesting = H, livestock = L, and harvesting + livestock = H + L). The analysis combined the SOC stock´s climatic, topographic, and above- and below-ground drivers. Data were evaluated using analyses of variance (ANOVAs), generalised linear models (GLMs), and principal component analyses (PCA). The results revealed significant differences (p < 0.001) in SOC stocks in forest types, soil types, and human impacts. The SOC stocks were higher in EV, NP, and ND-NB forests (SOC >119 tons ha−1) compared to MI and NA forests (SOC ∼100 tons ha−1). The highest SOC stocks were observed in U and H forests (SOC >125 tons ha−1), with Spodosols and Inceptisols showing the highest SOC levels among the soil types. The interaction between NP forests and harvesting presented a high SOC stock. PCAs identified two main groups influencing SOC variation: one related to climatic and topographic factors like seasonal temperatures and altitude and another associated with specific drivers such as pH, canopy cover, decaying wood, vascular plant cover, and lichen cover. We concluded that U and H forests in a region with high SOC stocks maintain equivalent SOC storage. However, special attention is needed for forest management practices involving integrated livestock in harvested forests.